2019
DOI: 10.1161/circresaha.119.315380
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Monocyte Chemoattractant Protein-1 and Risk of Stroke

Abstract: Georgakis et al. Circulating monocyte chemoattractant protein-1 and risk of stroke: a meta-analysis of population-based studies involving 17,180 individuals. Appendix I. Search strategy. Online Table I. Summary of the study design, population characteristics, methods used for quantifying circulating MCP-1 levels, stroke outcome definitions, and assessments in the cohorts included in the meta-analysis. Online Table II. Quality characteristics of the included studies according to the Newcastle-Ottawa Scale. Onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 43 publications
2
56
0
1
Order By: Relevance
“…Our findings corroborate earlier studies that showed CRP had no clear effect on ICH risk ( Liu et al, 2014 ). Similar results were also found in a meta-analysis consisting of six population-based prospective studies ( Georgakis et al, 2019 ). Another meta-analysis has also suggested that elevated baseline CRP levels exhibited no clear effect on HS ( Zhou et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Our findings corroborate earlier studies that showed CRP had no clear effect on ICH risk ( Liu et al, 2014 ). Similar results were also found in a meta-analysis consisting of six population-based prospective studies ( Georgakis et al, 2019 ). Another meta-analysis has also suggested that elevated baseline CRP levels exhibited no clear effect on HS ( Zhou et al, 2016 ).…”
Section: Discussionsupporting
confidence: 86%
“…Monocyte chemoattractant protein-1 (MCP-1/CCL2) is a member of the C-C chemokine family, and the receptor(s) for MCP-1 is CCR2, which mediates monocyte chemotaxis via regulation of calcium mobilisation and inhibition of adenylyl cyclase [ 8 ]. MCP-1 is considered as a marker and therapeutic target of atherosclerosis [ 9 , 10 ]. The mRNA expression of the MCP-1 is upregulated in human atherosclerotic plaques [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, MCP-1 may be secreted by neutrophils and expressed by endothelial cells of cardiac or neural tissue vessels, even in the absence of stimulation by MCP-1 specific cytokines (IL-1) and blood components [ 46 , 47 ]. The predictive value of MCP-1 instead of CRP was also reported in studies devoted to biomarkers of community-acquired pneumonia [ 47 ], hemorrhagic stroke and cardiovascular disease (CVD) mortality [ 48 , 49 ]. In the latter study, hsCRP was not related to CVD ( p = 0.22), and MCP-1 showed a trend significantly associated with CVD mortality in an age- and sex-adjusted multivariable analysis ( p = 0.059).…”
Section: Discussionmentioning
confidence: 92%